Investigating viscoelastic postseismic deformation due to large earthquakes in East Anatolia, Turkey. (March 2016) - Sunbul, Fatih; Nalbant, Suleyman S.; Simão, Nuno M.; Steacy, Sandy
Abstract: We investigate the postseismic viscoelastic flow in the lower crust and upper mantle due to the 19th and 20th century large earthquakes in eastern Turkey. Three possible rheological models are used in the viscoelastic postseismic deformation analysis to assess the extent to which these events influence the velocity fields at GPS sites in the region. Our models show that the postseismic signal currently contributes to the observed deformation in the eastern part of the North Anatolian fault and northern and middle parts of the East Anatolian Fault Zone, primarily due to the long-lasting effect of the M s 7.9 1939 earthquake. None of the postseismic displacement generated by the M s 7.5 1822 earthquake, which is the earliest and the second largest event in the calculations, exceeds observed error range at the GPS stations. Our results demonstrate that a postseismic signal can be identified in the region and could contribute up to 3–25% of the observed GPS measurements.